Multimodal Analysis of Thai Life Insurance’s “The Gift” Advertisement on Youtube: a Semiotic and Emotional Study in Visual Communication - Indra, Indra; Sutarman, Sutarman (International Journal Labs, 2025)
This research paper presents a comprehensive multimodal analysis of Thai Life Insurance’s renowned YouTube advertisement titled “The Gift.” The study aims to explore the intricate ways in which visual communication, through semiotic and emotional frameworks, constructs meaning and evokes affective responses in viewers. By employing semiotic theory alongside emotional response analysis, this paper investigates how the advertisement’s visual and narrative elements function synergistically to convey cultural values, social messages, and emotional resonance. Central to this analysis are the advertisement’s use of color symbolism, narrative structure, and emotional triggers, which are examined to understand their role in shaping audience interpretation and engagement.The methodology integrates qualitative content analysis and multimodal discourse analysis, focusing on the advertisement’s visual signs, symbolic codes, and emotional cues. The semiotic analysis deciphers the layers of meaning embedded in imagery, color palettes, and symbolic motifs, while the emotional analysis assesses how these elements stimulate affective reactions, fostering empathy and connection with the brand’s message. Key findings reveal that “The Gift” effectively employs culturally significant colors and a compelling narrative arc to elicit profound emotional responses, reinforcing Thai Life Insurance’s brand identity and social commitment. This study contributes to the broader field of visual communication by demonstrating the power of multimodal strategies in advertising to engage audiences both cognitively and emotionally, offering insights for scholars and practitioners interested in the intersection of semiotics, emotion, and marketing communication. The inclusion of diagrams illustrating semiotic models and emotional response charts further enriches the analytical depth of this research.